Stress Coping Strategies for Parents Who Have Speech Delay Children - Janah, Roudotul; Yunitasari, Septiyani Endang (Mataram University, 2024)
Parenting stress is a psychological aversive condition and physiological reaction that arises as a result of parental pressure in the parenting pattern of a speech delayed child. Efforts that can be made when experiencing parenting stress include coping strategies. The aim of the research is to find out a description of stress coping strategies for parents who have speech delayed children and a description of the counseling process that should be given to parents who experience stress because they have speech delayed children. Qualitative research method with phenomenological design. The respondents used consisted of three parents who had speech delayed children. Data collection techniques through observation and in-depth interviews. Data analysis by means of data reduction, data presentation and drawing conclusions. The results of this study indicate that the description of stress coping strategies for parents who have speech delayed children is using a combined coping strategy, namely problem focused coping strategies and emotion focused coping strategies and process descriptions. Counseling that should be given to parents who experience stress due to having a speech delayed child using group intervention activities related to coping stress strategies has been proven to be effective in reducing the level of stress experienced.